Art of Composers of Fergana Valley the Continuity and Endurance of Their Traditions - Marifatkhon, Khuraliyeva; Ugli, Orifjonov Husniddin Sohibjon (International Journal on Integrated Education, 2023)
Abstract; This article looks at the art of composition, which is considered a genre of music of the Uzbek people, and its history. In addition, attention was paid to the development of the art of composition, representatives of the Fergana Valley School of Composition and their compositional activities.